Early Implementation of Universal Health Coverage Among Hypertension Subjects in Sleman District of Yogyakarta - Rita Suhadi; Yunita Linawati; Dita M Virginia; Christianus H Setiawan (Acta Medica Indonesiana, 2015)
Aim: to evaluate the participant rate of the new universal health coverage (UHC) and its impact on the hypertensive subjects from the rural area in the Sleman-District of Yogyakarta during the early implementation. Methods: this epidemiological survey of the new UHC implementation was included as an analytical crosssectional study done with cluster random sampling. The subject criteria were aged 30-85 year, not in pregnancy, and signed the informed-consent. Subjects were grouped based on the health coverage disparity and analyzed with chi-square statistics for the hypertension prevalence, awareness, therapy, and control. The additional variables of BMI, education, occupation, income, smoking, diet control, physical activity, and health facilities were grouped into binomial data and analyzed based-on the health coverage disparity. Results: of 926 total subjects, 602 (65.0%) subjects had the health coverage including 9.2% of the new UHC. The groups of with and without health coverage were not significantly different in hypertension prevalence, the profile of age, blood pressure, and the proportion of the other variables (p>0.05) except for smoking and physical activities. In the high blood pressure sub-group (n=446), the subjects without health coverage had lower proportion of the hypertension awareness p<0.02; OR: 0.60 (CI95%:0.39-0.91) and therapy p<0.03; OR: 0.50 (CI95%:0.27-0.94), but not in the blood pressure control (p>0.05). Conclusion: the participant rate of new UHC was relatively low at 9.2%. Among the subgroup with ≥140/90mmHg blood pressure, the subjects without health coverage were more likely to have lower hypertension awareness and suboptimal therapy than those with the health coverage program.